2020
DOI: 10.1016/j.physletb.2020.135256
|View full text |Cite
|
Sign up to set email alerts
|

Decay properties of 22Ne + α resonances and their impact on s-process nucleosynthesis

Abstract: The astrophysical s-process is one of the two main processes forming elements heavier than iron. A key outstanding uncertainty surrounding s-process nucleosynthesis is the neutron flux generated by the 22 Ne(α, n) 25 Mg reaction during the He-core and C-shell burning phases of massive stars. This reaction, as well as the competing 22 Ne(α, γ) 26 Mg reaction, is not well constrained in the important temperature regime from ∼0.2-0.4 GK, owing to uncertainties in the nuclear properties of resonances lying within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(131 citation statements)
references
References 43 publications
(204 reference statements)
6
124
1
Order By: Relevance
“…The new evaluation of the reaction rate, based on spin-parity assignments by Jayatissa et al (2020) combined with data from Ota et al (2020), resulted in lower rates than previous evaluations, especially at low temperatures (see Figure 7). The lower rate is also the result of excluding an excited state at E x 11.112 MeV, corresponding to E α,lab 598 keV, observed by Massimi et al (2017) and not observed in these studies.…”
Section: State-of-the-artmentioning
confidence: 76%
See 1 more Smart Citation
“…The new evaluation of the reaction rate, based on spin-parity assignments by Jayatissa et al (2020) combined with data from Ota et al (2020), resulted in lower rates than previous evaluations, especially at low temperatures (see Figure 7). The lower rate is also the result of excluding an excited state at E x 11.112 MeV, corresponding to E α,lab 598 keV, observed by Massimi et al (2017) and not observed in these studies.…”
Section: State-of-the-artmentioning
confidence: 76%
“…The continued interest in this reaction is demonstrated by two very recent experimental studies by Ota et al (2020) and Jayatissa et al (2020) with α transfer reactions: Ota et al (2020) studied the 22 Ne( 6 Li, d) 26 Mg in inverse kinematics, detecting outgoing deuterons and 25,26 Mg in coincidence. In addition, Jayatissa et al (2020) studied the 22 N( 7 Li, t) 26 Mg reaction.…”
Section: State-of-the-artmentioning
confidence: 99%
“…In addition to the Giesen and Talwar 22 Ne( 6 Li,d) 26 Mg data, the more recent 22 Ne( 6 Li,d) 26 Mg results from Texas A&M at 7 MeV/u (corresponding to a 6 Li beam energy of 42 MeV) [16] and the sub-Coulomb barrier transfer results at 1 MeV/u [15] both fail to observe a strongly populated state at around E x = 11.17 MeV. In the case of the sub-Coulomb transfer measurement, the non-observation of the state could be due to the state of interest having a high spin [15].…”
Section: Combining the Experimental Datamentioning
confidence: 96%
“…The other experimental study used the 22 Ne( 6 Li,d) 26 Mg transfer reaction in inverse kinematics at a beam energy of 7 MeV/u [16]. In this case the deuteron ejectiles were detected in an array of silicon detectors and the 25 Mg and 26 Mg recoils were detected at the focal plane of the MDM magnetic spectrograph.…”
Section: Mgmentioning
confidence: 99%
See 1 more Smart Citation